Fast interaction between AMPA and NMDA receptors by intracellular calcium. Issue 6 (December 2016) - Rozov, Andrei; Burnashev, Nail
Graphical abstract: Highlights: An increase in [Ca 2+ ]i causes a reversible Ca 2+ -induced inactivation of NMDAR currents. Ca 2+ influx during unitary NMDAR-mediated synaptic events produces detectable self-inhibition on a time scale of a few milliseconds. Recombinant Ca 2+ -permeable AMPAR and Ca 2+ -impermeable NMDAR mutant channels were co-expressed in HEK 293 cells. The results show that Ca 2+ influx through Ca 2+ -permeable AMPARs may inhibit NMDAR on the time scale of synaptic transmission. Abstract: Suppression of NMDA receptor (NMDAR)-mediated currents by intracellular Ca 2+ has been described as a negative feedback loop in NMDAR modulation. In the time scale of tenths of milliseconds the depth of the suppression does not depend on the Ca 2+ source. It may be caused by Ca 2+ influx through voltage-gated calcium channels, NMDAR channels or release from intracellular stores. However, NMDARs are often co-expressed in synapses with Ca 2+ -permeable AMPA receptors (AMPARs). Due to significant differences in activation kinetics between these two types of glutamate receptors (GluRs), Ca 2+ entry through AMPARs precedes full activation of NMDARs, and therefore, might have an impact on the amplitude of NMDAR-mediated currents. The study of Ca 2+ -mediated crosstalk between AMPAR and NMDAR in native synapses is challenging due to high NMDAR Ca 2+ permeability. Therefore, recombinant Ca 2+ -permeable AMPAR and Ca 2+ -impermeable NMDAR mutant channels were co-expressed in HEK 293 cells to examine their interaction. An AMPAR-mediated increase in intracellular Ca 2+ concentration ([Ca 2+ ]i ) reversibly reduced the size of NMDAR-mediated whole-cell currents. The time course of the NMDAR channel inactivation and recovery from inactivation followed the time course of the [Ca 2+ ]i transient. When brief (1 ms) pulses of glutamate were applied to outside-out patches, the degree of NMDAR inactivation increased with the increase in charge carried by the currents through co-activated AMPARs. However, AMPAR-mediated NMDAR inactivation was abolished in the presence of intracellular fast Ca 2+ buffer BAPTA or in Ca 2+ -free extracellular solution. We conclude that Ca 2+ entering through AMPARs inactivates co-localized NMDARs in the time range of excitatory postsynaptic currents.